42.2: Photolithographic Patterning of Short Channel Organic TFTs for Displays. (28th November 2018) - Jeon, Jaekwon; Li, Xiuling; Choi, Jonghyun; He, Mingqian; Manley, Robert; Chang, Jaemyung; Zhelev, Nikolay; Mehrotra, Karan; Jang, Jin
Abstract : We report high‐performance organic TFTs with short channel length (L) of 6 µm. The OTFTs employ a bottom‐gate, bottom‐contact structure, with all layers patterned by conventional photolithographic methods. A field effect mobility of ∼0.45 cm 2 /V·s, and the on‐to‐off current ratio of ∼10 6 were obtained in the fabricated p‐channel OTFTs. The short channel OTFT with excellent performance is promising for flexible, high‐resolution displays.